Kualitas Semen Babi yang ditambahkan Antioksidan Semangka Merah (Citrullus Lanatus) - Loe, Nadya Putri Melvin; Tophianong, Tarsisius C; Foeh, Nancy D.F.K (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
This study is aimed at recognizing the effect that the addition of juice from watermelon (Citrulus lanatus) as antioxidants against motility and semen viability of pigs. The source of cement used in research came from the landrace boar. The semen of the pig was collected using the method of massage with the help of dummy sow. Cement is macroscopic and microscopic. The natural dilution material used is lontar. The treatment of the juice of 100 µL/10 mL, 200 µL/10 mL, 300 µL/10 mL, 400 µL/10 mL, 500 µL/10 mL. Liquid semen evaluations are performed every two hours after storage and sperm motility and viability evaluations of spermatozoa. The addition of watermelon juice (Citrulus lanatus) P3 treatment group at a dose of 300 µL/10mL has the best possible result in sustaining the motility of spermatozoa.